EXPLORING MOBILE BANKING ADOPTION IN INDONESIAN ISLAMIC BANKS: AN APPLICATION OF THE UTAUT2 MODEL - Mainata, Dedy; Septia, Rita; Giovani, Revi Mariska (UIN Raden Mas Said Surakarta, 2025)
Users of smartphones, PDAs, or other mobile devices can independently perform financial transactions via mobile banking anytime and anywhere. This study aims to understand the factors influencing customer adoption and continued usage of mobile banking services in Indonesia by applying the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), which considers user experience, gender, age, and education level as moderating variables. Data were collected through a structured questionnaire distributed both online and offline to 226 users of Islamic bank mobile banking services in Indonesia. Selected using a non-probability purposive sampling method, targeting individuals with prior experience in using mobile banking. The sample consisted of respondents from various provinces across Indonesia, predominantly from Java and Kalimantan, with diverse backgrounds in terms of age (mainly aged 30–40 years). The data were analyzed using Smart PLS 4 software. The findings reveal that effort expectancy, habit, hedonic motivation, and social influence significantly influence the adoption and use of mobile banking services. The demographic analysis indicates that users with master’s degrees and those in the 30–40 age group are the most likely to adopt these services. These findings provide strategic insights for Islamic financial institutions aiming to maintain and enhance customer engagement with mobile banking. This study offers a novel contribution to academic discourse and delivers actionable recommendations for policymakers and banking practitioners to design inclusive and Sharia-compliant digital transformation strategies.